Intraoperative Vagus Nerve Monitoring: A Transnasal Technique during Skull Base Surgery - Schutt, Christopher A.; Paskhover, Boris; Judson, Benjamin L. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives Intraoperative vagus nerve monitoring during skull base surgery has been reported with the use of an oral nerve monitoring endotracheal tube. However, the intraoral presence of an endotracheal tube can limit exposure by its location in the operative field during transfacial approaches and by limiting superior mobilization of the mandible during transcervical approaches. We describe a transnasal vagus nerve monitoring technique.Design and Participants Ten patients underwent open skull base surgery. Surgical approaches included transcervical (five), transfacial/maxillary swing (three), and double mandibular osteotomy (two). The vagus nerve was identified, stimulated, and monitored in all cases.Main Outcome Measures Intraoperative nerve stimulation, pre- and postoperative vagus nerve function through the use of flexible laryngoscopy in conjunction with assessment of subjective symptoms of hoarseness, voice change, and swallowing difficulty.Results Three patients had extensive involvement of the nerve by tumor with complete postoperative nerve deficit, one patient had a transient deficit following dissection of tumor off of nerve with resolution, and the remaining patients had nerve preservation. One patient experienced minor epistaxis during monitor tube placement that was managed conservatively.Conclusions Transnasal vagal nerve monitoring is a simple method that allows for intraoperative monitoring during nerve preservation surgery without limiting surgical exposure.
Keywords: intraoperative nerve monitoring; vagus nerve; nerve preservation; skull base surgery